Misinformation Disguised as Humor: Deepfakes’ Impact on Instagram Trust - Fuente-Alba Cariola, Fernando; Torres Aravena, Claudio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research analyzes the impact of deepfakes or fake videos generated by artificial intelligence on Instagram's trust, in Concepción, Chile. In addition to analyzing the deepfakes, a focus group and a questionnaire were applied to more than 100 people. Among the results, it stands out that 85.2% of the participants have seen at least one deepfake video on Instagram. When they identify it, more than half of them laugh when they see it. 57.6% admit to doubting its authenticity and 81.4% indicated that deepfakes affect their trust in Instagram.